THE ROLE OF MARITIME AND COMMERCIAL PILLARS: THE GLORY OF THE MAJAPAHIT KINGDOM IN 1350-1389 - Maria Mahdalena Efi Arfianti; Muhammad Iqbal Birsyada (SOSIOEDUKASI, 2026)
This study examines the important role of maritime power and trade in supporting the political and economic supremacy of the Majapahit Kingdom during the reign of Hayam Wuruk (1350–1389 AD). Using historical literature research methods, this study went through four stages, namely heuristics, verification, interpretation, and historiography. The results of the study show that Majapahit successfully integrated a strong maritime defense system with a structured trade network. The kingdom strategically positioned its naval forces in various maritime zones and optimized river infrastructure, particularly the Brantas and Bengawan Solo rivers, to connect inland production areas with major ports such as Canggu, Tuban, Gresik, and Surabaya. Additionally, Majapahit applied the diplomatic principle of Mitreka Satata in establishing peaceful and stable relations with regional and inter-regional kingdoms, such as China, India, and Southeast Asian nations. This approach created a safe and profitable trading environment. As a result, Majapahit emerged as a dominant maritime and commercial power in the 14th century, demonstrating that the maritime and trade sectors were the cornerstone of the kingdom's prosperity